“Forces for peace because of the magic in them”: Processes of Anglo-Soviet musical exchange c.1959-1974 - Isobel Thompson (Slovo, 2021)
Musical histories of the Cold War frequently emphasise the impact of American musical tours to socialist countries and the ‘weaponisation’ of modernist music, supposedly representative of the cultural freedom exclusive to the capitalist West, against the strict confines of Socialist Realism. This narrative, however, denies the vast output of classical music from the USSR and the brilliance of Soviet classical musicians, who consistently dominated international music competitions. This paper explores the British reception of visiting Soviet classical musicians to the UK from a multi-layered perspective. Starting with an analysis of the ways Anglo-Soviet musical exchanges were carried out through official government agreements, it goes beyond the traditional political focus to highlight the hitherto neglected role of British impresarios Victor and Lilian Hochhauser in coordinating Anglo-Soviet musical exchanges, and their fundamental importance to the success of such performances in Britain. It also examines interactions between Soviet and British musicians, and the relevance of these relationships to cultural diplomacy more broadly. The final section explores how Soviet music was presented to British audiences in programme notes and received in the broadsheet press.
Keywords: music; Soviet music; musical exchange; Anglo-Soviet exchange; Hochauser